Understanding Age-Related Differences in Grammar Perception Among Children with Developmental Language Disorder - Georgiou, Georgios P.; Theodorou, Elena (My University, 2026)
Objectives: This study examines how Cypriot Greek children with developmental language disorder (DLD) perceive grammatical structures, with a focus on the influence of age. Methods: Fourteen children with DLD and 14 typically developing (TD) children, aged 7;10 to 10;4, participated in grammaticality judgment tasks. To control for age and condition, the children were divided into four groups: younger children with DLD, younger children with TD, older children with DLD, and older children with TD. Results: Younger children with DLD performed worse on grammaticality tasks compared to their TD peers, while older children with DLD performed comparably to older TD children. Both younger DLD and TD groups exhibited lower performance than their older counterparts. Conclusions: These findings highlight that grammar perception may serve as a diagnostic marker of DLD. Furthermore, the improved performance in older children indicates a developmental trajectory in language skills, likely supported by ongoing brain maturation and the possible presence of a cognitive mechanism that enables children with DLD to gradually develop compensatory strategies.
Keywords: Age; Developmental language disorder; Grammar; Perception